Proposed new interior design of Alienware PC Centre, for Dell Malaysia at Lot S-20, Level 2, Nineteen Digital Mall, USJ 19, Persiaran Kewajipan, Subang Jaya Selangor / Muhamad Zaidi Jamil - Jamil, Muhamad Zaidi (2010)
A final year student pursuing a diploma course in Interior Design is required to prepare a final year project. All the design must be related to the project that have been choose. Before doing the design, main aspect must be consider to get the information. So that, we must do a research, case study, design schematic and the planning to make sure that client will give the good feedback with our design. Because of that, the systematic work must been done properly start from the design development until the end of the project. Proposed new interior design of Alienware Pc Centre is a one of the advantages to the client for introduce their product to all Malaysian. It is because Alienware is a new products in Malaysia. They also want to attract the peoples come to their centre. Followed the objective and the issues, a space planning was come out with the design concept and the images. So, to implement the design into the space is a complicated way because it have the stages we must follow. The planning that we have been create and the ideas that we want to implement into the space must be related to the concept and the images. With the concept Disclose, Discover, Differentiate and the ultra-modern images will implement into the space and the building that have been analysis will be used as clients approval. So, conclusion is, the good design is how we implement the concept and the images into the design centre, followed by the development of ideas.